Cowboy life: reconstructing an American myth - Savage, William W., editor; University Press of Colorado, publisher (Colorado State University. Libraries, 1993)
Selected narratives and photographs provide a composite view of cowboy life in late nineteenth-century Texas, the Indian Territory, and Kansas, illuminating the persisting mythic image of the cowboy in American culture.
Anger and bad whiskey urge him on to deeds of blood and death / Joseph G. McCoy -- Most reckless of all the reckless desperadoes / Richard Irving Dodge -- Among cowboys are to be found the sons of the best families / Walter Baron Von Richthofen -- I spend my last dime for a glass of lemonade / Charles A. Siringo -- Creature of circumstance / Joesph Nimmo, Jr. -- Man of unflinching courage / Charles Moreau Harger -- There are cowboys and cowboys / Ricahrd Harding Davis -- Cow-boy goes to the school of nature / W.S. James -- Wilderness was a source of great joy to the cowboys / Baylis John Fletcher -- He becomes deeply and famously drunk / Alfred Henry Lewis -- No class of men ever was so unfaithfully represented / National Livestock Association -- Dead tough men bawled like babies / Andy Adams -- I am glad I had the experience / Frank Collinson.
Edited and with a new preface and afterword by William W. Savage, Jr.
Keywords: Cowboys -- West (U.S.)